Hydatidiform mole and surviving coexistent twin (a case report) - S.Bakhshandeh-Nosrat (MD); R.Azarhoush (MD) (مجله دانشگاه علوم پزشکی گرگان, 2005)
Hydatidiform mole with a coexistent fetus is a rare occurrence with an incidence of 1 per 22000-100000 pregnancies. It is associated with persistant gestational trophoblastic tumor. Hence an early and correct diagnosis is imperative to plan subsequent management of such patients. We report a case of primigravida who presented with vaginal bleeding and severe nausae and vomiting. Expectant management was carried out for her pregnancy with finally ended in abortion.